2000
DOI: 10.1007/bf03343668
|View full text |Cite
|
Sign up to set email alerts
|

DHEA-S levels in hypopituitaric patients with severe GH deficiency are strongly reduced across lifespan. Comparison with IGF-I levels before and during rhGH replacement

Abstract: Both IGF-I and DHEA-S undergo an age-related decrease and their decrease could be involved in age-related changes in body composition, structure functions and metabolism. On the other hand, it is well known that mean IGF-I levels are clearly reduced in hypopituitaric patients with GH deficiency (GHD) while data about dehydroepiandrosterone sulfate (DHEA-S) levels in hypopituitarism are scanty. We evaluated DHEA-S and IGF-I levels and their relationship in 90 patients with panhypopituitarism (HYPOPIT) with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the present study, the dose of hGH required to obtain a similar response in IGF‐I tended to be lower in ACTH‐sufficient patients than in ACTH‐deficient patients, although the groups also differed in the percentage of patients on oestrogen replacement therapy. Previous studies have shown a positive correlation between DHEAS and IGF‐I levels (Morales et al ., 1994), also described in hypopituitary patients (Aimaretti et al ., 2000). In our study, DHEAS was significantly different between the two groups; it seems possible that the higher DHEAS levels in the ACTH‐sufficient patients may have had a favourable effect on IGF‐I generation.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the present study, the dose of hGH required to obtain a similar response in IGF‐I tended to be lower in ACTH‐sufficient patients than in ACTH‐deficient patients, although the groups also differed in the percentage of patients on oestrogen replacement therapy. Previous studies have shown a positive correlation between DHEAS and IGF‐I levels (Morales et al ., 1994), also described in hypopituitary patients (Aimaretti et al ., 2000). In our study, DHEAS was significantly different between the two groups; it seems possible that the higher DHEAS levels in the ACTH‐sufficient patients may have had a favourable effect on IGF‐I generation.…”
Section: Discussionmentioning
confidence: 80%
“…Information regarding serum adrenal androgen levels in GH‐deficient individuals has been conflicting and limited to a small number of reports mainly derived from studies performed in children (Cohen et al ., 1981; Ilondo et al ., 1982b; Lew et al ., 1988; Juul et al ., 1998). There are few studies available showing decreased adrenal androgen levels in adult panhypopituitary patients (Young et al ., 1997; Aimaretti et al ., 2000; Miller et al ., 2001). The present study demonstrates that even adult patients with partial hypopituitarism who are ACTH‐sufficient, have decreased serum DHEAS levels despite maintaining normal basal and stress‐stimulated cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found low DHEA-S levels in all 35 patients with hypopituitarism, implying that a DHEA-S concentration above 53.5 ug/dl (1.4 umol/l) makes the diagnosis of corticotropin deficiency extremely unlikely [17]. However, in the second study, some overlap of DHEA-S concentration in corticotropin deficient patients and those in normal subjects was found [18]. Partial corticotropin deficiency in some patients might explain these discrepant results.…”
Section: Corticotropin Deficiencymentioning
confidence: 81%
“…In addition to the oncogenic activity of RET , several RET polymorphisms have been described in patients with PDA, most of them resulted in enhanced activation of downstream RET signaling . Genetic studies revealed higher allelic frequency of certain single nucleotide polymorphisms (SNPs) in cancer compared to normal controls . These SNPs are associated with increased sensitivity of RET to its ligand GDNF, and increased MAPK pathway activation .…”
Section: Introductionmentioning
confidence: 99%